A comparative study on the retentive capacities of non pin-retained and pin-retained complex amalgam restorations - Catalan, Cynthia Julia B.; Santos, Regina Isabel B.; Macasaet, Avelino (Adviser).; Guerrero, Leticia P. (Adviser).; Estaniel, Cynthia P. (Adviser).; Reyes, Rannier F. (Adviser).
The use of pins can cause harmful effects to the tooth such as dentin crazing, fractures, internal stresses and microleakage. Moreover, pins are very expensive to use. Therefore alternatives to pin placement should be considered. More conservative approaches are the Amalgapin and the Dentinal Slot techniques. The amalgapin technique involves boring dentin chambers that are 1 mm wide, 2 mm deep and 0.5 mm into the dentino-enamel junction. One dentin chamber per missing cusp is used. The dentinal slot technique uses a 33 1 2 inverted cone bur to bore a continuous hole horizontally along the gingival floor. The dimensions of the slot is therefore the same as the 33 12 inverted cone bur. Result of this study show that pin retained restorations are about three times more retentive than non pin retained restorations. But since there are still no recorded values for the minimum and maximum tensile forces in the mouth, it cannot be concluded that the tensile strengths of the non pin retained restorations are not sufficient enough to last in the mouth. Further studies need to be done on this.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental amalgams